Modulation of Autophagy and Mitochondrial Dynamics Gene Expression by Turmeric and Mangosteen Peel Extract - Diana Krisanti Jasaputra; Julia Windi Gunadi; Cliff Aaron Sutiono; Ronny Lesmana (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2023)
High fat diet (HFD) induces oxidative stress and mitochondrial dysfunction which culminates in fatty liver disease. Autophagy and mitochondrial dynamics are affected by HFD. Turmeric and mangosteen have potential roles as antioxidants and regulators of mitochondrial function in the liver. The study aims to examine the effect of turmeric and mangosteen peel extract on autophagy and mitochondrial dynamics in the liver after HFD induction. Five groups of animals (n=5) as used: negative control, positive control (HFD), turmeric (HFD + 270 mg/kg BW turmeric extract), mangosteen (HFD + mangosteen 270 mg/kg BW peel extract), and fenofibrate (HFD + 15 mg/kg BW fenofibrate). HFD was given for 7 weeks, continued by another 7 weeks plus treatment. Liver sections were extracted to conduct semi-quantitative PCR. Autophagy (LC3, p62), mitophagy (Pink1, Parkin, Bnip3), mitochondrial fission (Drp1, Fis1), and mitochondrial fusion (Opa1, Mfn1, Mfn2) gene expression were measured. LC3 (p=0.048), p62 (p=0.043), Pink1 (p=0.012), Bnip3 (p=0.010), Mfn1 (p=0.015), and Mfn2 (p=0.035) gene expressions were differed significantly, while Parkin (p=0.098) Drp1 (p=0.962), Fis1 (p=0.570), and Opa1 (p=0.055) gene expressions did not differ between groups. Both turmeric and mangosteen peel extract have positive effects by activating autophagy, mitophagy, and mitochondrial fusion in rat liver induced by HFD.